Distinct Treatment Outcomes of Antiparasitic Therapy in Trypanosoma cruzi-Infected Children Is Associated With Early Changes in Cytokines, Chemokines, and T-Cell Phenotypes - Albareda, María C.; Natale, María A.; De Rissio, Ana M.; Fernandez, Marisa; Serjan, Alicia; Alvarez, María G.; Cooley, Gretchen; Shen, Huifeng; Viotti, Rodolfo; Bua, Jacqueline; Castro Eiro, Melisa D.; Nuñez, Myriam; et al. (Frontiers in Immunology, 2018)
Background: In contrast to adults, Trypanosoma cruzi-infected children have more broadly functional Trypanosoma cruzi-specific T cells, and the total T-cell compartment exhibits fewer signs of immune exhaustion. However, not much is known about the link between immunocompetence and the treatment efficacy for human Chagas disease. Methods: Using cytokine enzyme-linked immunosorbent spot (ELISPOT) polychromatic flow cytometry, cytometric bead assay, multiplex serological assays and quantitative PCR, we evaluated T. cruzi-specific T-cell and antibody immune responses, T-cell phenotypes and parasitemia in children in the early chronic phase of Chagas disease undergoing anti-Trypanosoma cruzi treatment. Results: Treatment with benznidazole or nifurtimox induced a decline in T. cruzi-specific IFN-γ- and IL-2-producing cells and proinflammatory cytokines and chemokines. T-cell responses became detectable after therapy in children bearing T-cell responses under background levels prior to treatment. The total frequencies of effector, activated and antigen-experienced T cells also decreased following anti-T. cruzi therapy, along with an increase in T cells expressing the receptor of the homeostatic cytokine IL-7. Posttreatment changes in several of these markers distinguished children with a declining serologic response suggestive of successful treatment from those with sustained serological responses in a 5-year follow-up study. A multivariate analysis demonstrated that lower frequency of CD4+CD45RA−CCR7−CD62L− T cells prior to drug therapy was an independent indicator of successful treatment. Conclusions: These findings further validate the usefulness of alternative metrics to monitor treatment outcomes. Distinct qualitative and quantitative characteristics of T cells prior to drug therapy may be linked to treatment efficacy.